Plan de desarrollo turístico para el páramo Morro Pansache parroquia Mulalo provincia de Cotopaxi 2012 – 2013 - Velasco Chasipanta, Martha Beatriz (2013)
Having a Tourist Development Plan by Morro Pansache Highland Association and the bumping Zone of highland, appear a necessity to optimizing management capacity for the sustainable use of its natural, cultural resources, and to fortify the new pillars for the equitable construction and solidary community by tourism. Fulfilling this wish the first technical instrument is acquired, which one helped to discover the next: first chapter contains diagnose situational of Mulaló Parish, which are allow to identify the current situation in socio economic, cultural, tourist and environmental way, determining gaps and potentialities concerning to its tourist development. Besides, FODA scheme taking into account the strengths and weaknesses; opportunities and threats of Morro Pansache Highlands with the research of the strategic problems study and solutions. On the second chapter, the register of the tourist resources is developed identifying zone potential and its surroundings.